The illustrated atlas of the human body - McMillan, Beverly (Sydney : Weldon Owen, 2008)
Uses microphotography, advanced medical imaging, and annotated illustrations to provide scientific information about the human body, covering the body systems, bones, muscles and skin, sensory and digestive processes, and the brain and internal organs.
Keywords: Anatomy